Kadar Fenolat Total dan Aktivitas Antioksidan Ekstrak Kulit Batang Nyireh (Xylocarpus granatum J.Koenig) dengan Metode Spektrofotometri UV-Vis - Elfasyari, Trie Yuni; Afifah, Khairiani Afifah; Andayani, Regina (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2022)
There is a composition that has been known to have an important role in the treatment of disease is the composition of antioxidants. One of the antioxidant compositions is phenolic compounds, which are compounds contained in plants. From previous studies it is known that plants containing phenolic compounds are nyireh (Xylocarpus granatum J.Koenig) which are widely used by the community as traditional medicine for the treatment of various diseases. The purpose of this study was to determine the total phenolic levels contained in Nyireh as an antioxidant activity that can be useful for the body.Testing antioxidant activity using the Ferric Reducing Antioxidant Power (FRAP) method. Results of the study showed the highest value of phenolic content contained in nyireh bark extract was the value in ethyl acetate extract of 43.275% while the highest antioxidant activity was seen in the acetic sample of ethyl acetate nyireh stem bark amounting to 9.44 mmol of Fe (II)/100g.